Risk Factors For Hypertension Incidents At Puskesmas Sekip Palembang - Yanti, Efri; Nurjannah (Sahabat Publikasi Kuu, 2025)
Hypertension is a major public health issue that increases the risk of cardiovascular disease and premature death. This study aims to analyze the risk factors associated with the incidence of hypertension at Sekip Public Health Center (Puskesmas Sekip) in Palembang. This research employed a quantitative approach using an analytical observational method with a cross-sectional design, conducted from January 9 to February 9, 2025. Data were analyzed using non-parametric statistical tests (chi-square). The results showed that only age had a significant relationship with diastolic blood pressure (p=0.011), while there was no significant association between age and systolic blood pressure (p=1.000). Other factors, including body weight status, smoking history, diabetes history, hereditary disease history, stress history, regular eating patterns, and physical activity, showed no significant association with either systolic or diastolic blood pressure (all p-values > 0.05). In conclusion, among all analyzed risk factors, only age was found to significantly influence one component of blood pressure in hypertensive patients, specifically diastolic pressure.